Effects of Rhizopus addition on physicochemical indexes of fermented grains and flavor components of base liquor in Xiaoqu light-flavor Baijiu - WANG Ruixin, GAO Yudi, LIU Xiaomei, LI Jiajie, WANG Han, WANG Yupeng, WEI Chunhui, ZHANG Boqin, WU Xiaole, CHEN Yefu, XIAO Dongguang (Zhongguo niangzao)
In order to explore the effects of Rhizopus addition on the quality of Xiaoqu light-flavor (Qingxiangxing) Baijiu, the effects of different Rhizopus addition on the enzymatic activity and physicochemical factors of fermented grains, and the flavor components in the base liquor were analyzed by conventional analysis, gas chromatography and high performance liquid chromatography. The results demonstrated that Rhizopus addition predominantly affected enzymatic activities during the saccharification stage. With only Jiuqu addition 1% and no Rhizopus as the control group, when the Rhizopus addition was 0.5%, the saccharification enzyme activity (31.31 U/g) was significantly higher than that of control group (16.94 U/g) (P<0.05). The activity of acid protease (11.09 U/g) was significantly higher than that of control group (6.26 U/g) (P<0.05). The activity of liquefaction enzyme (0.38 U/g) was higher than that of control group (0.35 U/g), but not significant (P>0.05). When the Rhizopus addition was 0.5%, compared with the control group, the contents of acidity, residual sugar, amino acid nitrogen and ammonia nitrogen in fermented grains were the highest at the beginning of fermentation, which were increased by 18.43%, 14.31%, 14.24% and 47.98%, respectively. Additionally, with the Rhizopus increased, the ethyl acetate content in the base liquor gradually increased. By the end of fermentation (15 d), compared to the control group, the ethyl acetate content in the liquor sample with Rhizopus addition 0.5% had increased by 67.84%. In conclusion, Rhizopus addition 0.5% had the optimal effect. This study provided new insights for enriching the flavor profile of liquor and improving the quality of Xiaoqu light-flavor Baijiu.